Ventricular Peritoneal Shunting Using Modified Keen’s Point Approach: Technical Report and Cases Series - Elena Virginia Colombo; Daniele Bongetta; Fabio Cofano; Alessandro Versace; Diego Garbossa; Alessandro Bertuccio; Daniele Armocida; Patrizia d’Auria; Lisa Maria Farina; Roberto Assietti; Fulvio Tartara (Surgeries, 2022)
Background: Ventricular peritoneal shunting (VPS) is a frequent procedure in neurosurgery, unfortunately still burdened with a significant rate of complications. The frontal Kocher’s point is the most frequently used landmark for ventricular puncture. Keen’s point (posterior parietal approach) seems to be a valid alternative. We report a newly described access to the lateral ventricle located in posterior temporal area and the results of a large series of adult patients. Methods: Retrospective analysis of a series of 188 cases of VPS performed with this approach. Results: Mean surgical time was 51.5 +/− 13.1 min (range 25–90 min). Twenty-one patients (11.2%) were subjected to revision surgery: eight cases (4.3%) for displacement or malfunction of ventricular catheter, eight cases (4.3%) for abdominal issues, three cases (1.6%) for hardware failure, and two cases (1.1%) for infection. Optimal catheter placement was reached in 90.1%. Conclusions: The modified Keen’s point approach seems to be safe, technically feasible, and reproducible, showing some potential advantages such as short surgical time, precision in ventricular catheter placement, and short tunneling tract. The need for surgical revision is similar to that reported in the literature, while the rate of catheter malpositioning and infections seems to be low; hemorrhages around catheter and seizures were not reported.